A Multi-Disciplinary Inquiry of Secular and Christian Approaches to Sex Education. Issue 1 (2nd January 2018) - Yu, Chong Ho; Lee, Hyun Seo
ABSTRACT: Secular scholars have criticized Christian education and counseling on sex as restrictive, ineffective, and outdated. The authors of the current study explored both common non-Christian and Christian approaches to human sexuality with reference to overarching domains of religion, philosophy, psychology, sociology, and anthropology. Secular approaches were classified as the inward approach, the spatial approach, and the temporal approach, whereas Christian approaches were categorized as the traditional and the modern perspectives. Although Christian faith can be signified as a protective factor against casual and risky sexual behaviors, traditional Christian values should be reevaluated in favor of comprehensive Christian approaches to sexuality, which embrace sexual desires as divine gifts for completeness of humanity.